TRACE ELEMENTS IN INDIGENOUS MEDICINAL DIURETIC PLANTS IN HUMAN HEALTH AND DISEASE (CYMBOPOGON CITRATUS (DC) STAPF., RAPHANUS SATIVUS LINN. AND ZEA MAYS LINN.) - Mirza, Maryam; Yaqeen, Zahra; Bano, Alia; Qadri, R B; Qadiruddin, Muhammad (Biological Sciences - PJSIR, 2004)
Three indigenous medicinal plants reported to be diuretic have been selected for the study of trace elements and their possible role in human health. Twelve trace elements (Cu, Zn, Mn, Fe, Cu, Ni, Cd, Pb, Cr, Ag, Na and K) have been detected and estimated in ash of various parts (leaves of Cymbopogon citratus (DC) Stapf., seeds of Raphanus sativus Linn. and corn silk of Zea mays Linn.).